On the Hilbert problem for analytic functions in quasihyperbolic domains - Gutlyanskii, V.Ya.; Ryazanov, V.I.; Yakubov, E.; Yefimushkin, A.S. (Доповіді НАН України, 2019)
We study the Hilbert boundary-value
problem for analytic functions in the Jordan domains satisfying the quasi-hyperbolic
boundary condition by Gehring—Martio. Assuming that the coefficients of the problem are functions of the
countably bounded variation and the boundary data are measurable with respect to the logarithmic capacity, we
prove the existence of solutions of the problem in terms of angular limits. As consequences, we derive the corresponding
results concerning the Dirichlet, Neumann, and Poincaré boundary-value
problems for harmonic functions. Досліджено граничну задачу Гільберта для аналітичних функцій в жорданових областях, які задовольняють квазігіперболічну умову Герінга Мартіо. З припущенням, що коефіцієнти задачі є функціями
зліченно-обмеженої варіації і граничні дані є вимірними відносно логарифмічної ємності, доведено існування розв'язків задачі в термінах кутових границь. Як наслідки отримано відповідні результати для
крайових задач Діріхле, Неймана і Пуанкаре для гармонічних функцій. Исследована краевая задача Гильберта для аналитических функций в жордановых областях, удовлетворяющих квазигиперболическому условию Геринга Мартио. С предположением, что коэффициенты
задачи являются функциями счетно-ограниченной вариации, а граничные данные измеримы относительно логарифмической емкости, доказано существование решений задачи в терминах угловых пределов.
В качестве следствий получены соответствующие результаты для краевых задач Дирихле, Неймана и
Пуанкаре для гармонических функций.